Malaria: A Five Year Hospital Review At The University Of Benin Health Center, Benin-City - R.E.ESEWE; H.B.OSADOLOR (International Journal of Pharma and Bio Sciences, 2010)
Malaria has been reported to be the commonest cause of death after HIV/AIDS with 90% of world’s incidence occurring in Africa and one third of the disease is found in Nigeria. The aim of this study was to investigate the incidence of malaria fever amongst staff and students of the University of Benin over a five-year period (2002- 2006) with a review to providing a better understanding as to the progress being made in the fight against its scourge and thereafter recommend measures to combat it.Of the Fifty eight thousand, one hundred and sixty nine (58,169) cases that reported with symptoms, only fifteen thousand seven hundred and twenty (15,720) actually tested positive for malaria fever after a serological test was done. This figure represents 27% of clients provisionally diagnosed as suffering from malaria fever. There was high incidence among the females(51.5%) against (48.5%) in males who tested positive for malaria fever. The incidence was highest in 2003, with 47.2% positive cases, this steadily declined in 2005 to 2006 to 41% positive result screened cases. Adult had the highest incidence that is, 78% more than those between ages 0 – 18yrs with 22%. The review shows that the war against malaria can be won with persistent education and research into new trends and use of modern health facility.